Fast Track UML 2.0 - Scott, Kendall (Apress, 2012)
The Superstructure portion of the UML 2.0 specification with which I've been working is 7811 pages long. (Actually, it's "only" 632 pages long, but the point is that it's big.) This is the document that contains most of the "meat" that comprises the UML. However, the document is rather impenetrable for anyone who's not a "modeling junkie," which is basically why I wrote this book. In other words, I slogged my way through the spec so you don't have to.